2023
DOI: 10.3390/nu15040868
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adipocytokines Profile in Children Born Small and Appropriate for Gestational Age—A Comparative Study

Abstract: Background: Adipose tissue is not only a storage place for fat, but also an endocrine organ, secreting bioactive molecules which influence body metabolism. Such molecules are known as adipocytokines. In the past years the coincidence between adipocytokines and fetal growth restriction disorders was found. The aim of the study was to estimate serum levels of adiponectin, leptin and resistin in children born small for gestational age, compared to children born at an appropriate size for gestational age. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The influence of altered adiponectin levels on increased insulin secretion has previously been emphasized in many studies. Zamojska et al [32] found that adiponectin and leptin levels were significantly higher in the SGA group compared to the AGA group, while resistin values were comparable between the 2 groups of patients. According to the results of this study, adiponectin levels were negatively correlated with blood pressure.…”
Section: Discussionmentioning
confidence: 97%
“…The influence of altered adiponectin levels on increased insulin secretion has previously been emphasized in many studies. Zamojska et al [32] found that adiponectin and leptin levels were significantly higher in the SGA group compared to the AGA group, while resistin values were comparable between the 2 groups of patients. According to the results of this study, adiponectin levels were negatively correlated with blood pressure.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, another study which included 45 SGA children showed higher levels of resistin, and it was independently correlated with low birth weight [ 64 ]. Recently, a study of 35 SGA children and 25 AGA children failed to show any difference in resistin levels between these two groups [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we observed that the EUGR group had a different adipokine profile than the healthy group, characterized by lower levels of adiponectin and resistin and higher levels of leptin. Low birth weight has previously been linked with high leptin and low adiponectin levels [ 59 ]. However, some studies have reported inconsistent findings regarding resistin in relation to low perinatal weight and obesity or overweight [ 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low birth weight has previously been linked with high leptin and low adiponectin levels [ 59 ]. However, some studies have reported inconsistent findings regarding resistin in relation to low perinatal weight and obesity or overweight [ 59 , 60 , 61 , 62 ]. Therefore, the role of this adipokine in regulating insulin sensitivity and adipogenesis during the perinatal period is not yet fully understood [ 63 ].…”
Section: Discussionmentioning
confidence: 99%